IOT PEMANFAATAN INTERNET OF THINGS PADA SMARTHOME DENGAN MODEL SIMULASI PROTOTYPE: IOT - Kurnia, Eka; Pandia, Mahdianta; Sembiring, Berti Sari Br; Margaretta, Desi (Utility Project Solution, 2024)
Internet of Things has been a recent focus in technology discussion. This tecnology enables every devices we own to connect to the internet, allowing remote control throught smartphones or even voice commands. The development of iot extends beyond large industries like power grids and factories, reaching into everyday household electronics. For instance, light can now be connected to the internet. The final project involves designing and creating an internet controlled relay system with comamands sent throught a telegram bot. This project aims to implement iot tecnology in a simple and affordable manner. The control system utilizes the nodeMCU microcontroller with a two -channel relay output to remote turn light on and off via telegram.